Blaga možganska poškodba - izziv za nevropsihologa - Čižman Štaba, Urša (Rehabilitacija (Ljubljana), 2015)
Mild traumatic brain injury, also called concussion, constitutes a major part of all traumatic brain injuries. The consequences are evident in the physical, cognitive and other psycho-logical fields. Although the injury is considered as mild, it can have a significant impact on both the patient and his/her whole family and their quality of life. Due to the absence of objective clinical diagnostic methods, the injury is often overlooked. Neuropsychological treatment aids its identification and assessment of the degree of disability, as well as identi-fication of other factors that influence the outcome of recovery after mild traumatic brain injury. The paper highlights the role of neuropsychological treatment for the purpose of neuropsychological assessment and treatment of cognitive disorders, and the treatment of emotional and behavioral disorders using cognitive behavioral therapy. An important factor in the occurrence of prolonged symptoms of postconcussion syndrome are the so-called secondary gain motives. Malingering can be detected with appropriate psychological as-sessment.
Keywords: blaga nezgodna možganska poškodba; Brain Injuries; cognitive behavioral therapy; cognitive rehabilitation; Cognitive Therapy; kognitivna rehabilitacija; kognitivna terapija; kognitivna vedenjska terapija; mild traumatic brain injury; možganske poškodbe; neuropsychological assessment; Neuropsychology; nevropsihologija; nevropsihološka diagnostika